Management of infections in critically ill neutropenic cancer patients - Buchheidt, Dieter; Hummel, Margit; Engelich, Georg; Hehlmann, Rüdiger (Journal of critical care, 2004)
Because of improving antineoplastic treatment options with increasing cure rates, prolonging survival, and improving quality of life, the reluctance to admit patients with malignant disease to an intensive care unit is not justified; thus, the number of patients with malignancies treated in intensive care units rises. The use of more aggressive anticancer regimens leads to an increase of attendant infections, which are the most frequent and often life-threatening complications in cancer patients. A multidisciplinary practical approach to evaluation and treatment is needed to optimize treatment results and to meet the various diagnostic and therapeutic challenges in this subset of patients on an intensive care unit.